Numerical Analysis of Density-Driven Reactive Flows in Hele-Shaw Cell Geometry - Bekkouche, S.; Kadja, M. (Engineering, Technology & Applied Science Research, 2020)
In this paper, a two-dimensional numerical simulation of the unsteady state of a two non-isothermal immiscible liquids layer system filling a reactor formed by two closely spaced parallel glass sheets, which is called an Hele-Shaw cell, vertically oriented, with an expected neutralization reaction between an acid and a base in the lower layer, under the action of gravity, is studied. Attention is given on the general behavior of the complete temporal pattern evolution (velocity, temperature, and concentration profiles) and the identification of the exothermic reaction’s role in giving birth to chemo-hydrodynamic patterns that occur because of concentration gradients. The effects of gravity and changes in initial acid and base concentrations on the formed patterns were studied. The mathematical model governing the phenomenon was solved numerically by the CFD software package COMSOL Multiphysics, with the finite element method and a comparison with the experimental data was made. The results show that this numerical tool is promising for the understanding of the reactive instabilities happening when two immiscible fluids come into contact.